Design, synthesis and SAR studies of novel tacrine derivatives as potent cholinesterase inhibitors - Bhushanarao Dogga; Eeda Koti Reddy; C.S. Sharanya; J. Abhithaj; K.G. Arun; C.S. Ananda Kumar; K.S. Rangappa (Elsevier, 2022)
A series of tacrine-2-amide derivatives were synthesized and biologically evaluated for their acetylcholinesterase (AChE) inhibition studies. All synthesized compounds showed a good potency less than 100 ​nM. Of 11 analogues compounds 7b, 8a and 8c were found to exhibit good potency of 23.66 ​nM, 20 ​nM and 24.33 ​nM towards inhibition of acetylcholinesterase, respectively. Insilico study revealed that these compounds can bind strongly in catalytic active site (CAS) as well as peripheral active site (PAS) of enzyme. The docking results stated that the π-π stacking interaction, have a significant role in the protein-ligand binding and provide information about the binding enthalpy. The compound 7b shows good affinity with AChE, and possess a glide score of −10.38 ​kcal/mol and having a binding energy of −24.03 ​kcal/mol. The compound 7b showed interaction with Tyr341 and forming π-π stacking with Trp86. The compound 8a shows a glide score of −11.22 ​kcal/mol with a binding energy of −30.88 ​kcal/mol which is contributed by π-π stacking interaction with Trp86, and a hydrogen bond with amino group of tacrine with His447. The compound 8c showed a better glide score of −12.81 with binding affinity of −59.90 ​kcal/mol.